Ivan Pavlov : exploring the mysteries of behavior - Saunders, Barbara R. (Berkeley Heights, NJ : Enslow Publishers, 2006)
"Learn about the Russian scientist who introduced the idea of conditioned reflexes in behavior."--From source other than the Library of Congress
The mastermind -- Pavlov's calling -- Studying natural sciences -- The courtship of Seriphima -- The theory of the conditioned reflex -- Ivan Pavlov's Russia -- Building a legacy -- History shapes the legacy.
Includes bibliographical references and index.
Keywords: Pavlov, Ivan Petrovich, -- 1849-1936 -- Juvenile literature; Pavlov, Ivan Petrovich, -- 1849-1936.; Physiologists -- Russia (Federation) -- Biography -- Juvenile literature; Scientists -- Russia (Federation) -- Biography -- Juvenile literature; Physiologists; Scientists